Transfusion Reactions as an Indicator of Service Quality of Blood Transfusion in Sanglah General Hospital Denpasar Bali-Indonesia - Mulyantari, Ni Kadek; Subawa, Anak Agung Ngurah; Yasa, I Wayan Putu Sutirta (BALI MEDICAL JOURNAL, 2016)
Background: One of the fatal side effects of transfusion is transfusion reactions. The incidence of transfusion reaction in Sanglah Hospital is still relatively high and far from national target which is 0.01%. To achieve the target of quality, it is necessary to set up an active program so that the number of incidence of transfusion reactions can be decreased. Methods: Pre and post test interventional study was conducted for 6 months in Sanglah Hospital Bali. All nurses in wards which is blood product frequently used was involved in this study. The intervention in this study was in the form of education and training programs on the application of the closed system and cold chain in the distribution of blood products as well as improved service system. Results: The results showed a decline in the incidence of transfusion reactions occurred every month during the study. The incidence of transfusion reactions occurred each month was 0.77%, 0.56%, 0.5%, 0.49%, 0.45% and 0.38% respectively. The average reduction in the incidence of transfusion reactions was 0.08% every month. The type of transfusion reaction that occurred was 59% urticaria, 29% fever, 7% shortness of breath, 4% fever and chills, and 1% shock. Conclusion: Education and training programs on the application of the cold chain system and closed system in the distribution of blood products as well as the improvement of service system helped reduce the number of the incidence of transfusion reactions in Sanglah Hospital Bali.